Cause-and-Effect Relationship Analysis of Cocoa Pod Husk Composites in Water Absorption Process Parametric Evaluation: A DEMATEL Approach - Isaac Temitope Abiola; Victor Chidiebere Maduekwe; Sunday Ayoola Oke (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2021)
Polymer composites are expanding in scope and applications to water-based structures such as the ship's hull in ship vessels due to their resistance to water and satisfactory mechanical properties. Unforunately, few studies have tackled their water absorption properties. In this paper, a novel method, DEMATEL, is used to analyse the conflicting water absorption process parameters of cocoa pod husk composite using the cause and effect associations of the parameters. The parameters considered are particulate loading, initial weight, particulate weight, the weight of the matrix, and weight after 150 days and rate of water absorption. A comparison scale explains the extent of influence of a criterion on the other. The direct relationship matrix is normalized and the total relation matrix generated to procedure a causal diagram. The most fascinating findings of the study are the differences between the sum of row and columns, which places particulate weights as the most appealing, 1.0798, while the rate of water absorption as the least appealing criterion. Besides, the sum of the row and column that yields the most attractive results is the particulate weight (5.4982) while the least attractive result is the rate of water absorption (3.5436). The novelty of this work lies in the application of DEMATEL structure to examine contextual associations between the essential pointers of water absorption process parameters, for cocoa pod husk composites in the water environment. To our knowledge, it is the first type of work in this area on the selected agro-filler-based composite.